Nurse led home-based care for people with HIV/AIDS - Elizabeth M. Wood; Babalwa Zani; Tonya M. Esterhuizen; Taryn Young (BMC, 2018)
Abstract Background Home-based care is used in many countries to increase quality of life and limit hospital stay, particularly where public health services are overburdened. Home-based care objectives for HIV/AIDS can include medical care, delivery of antiretroviral treatment and psychosocial support. This review assesses the effects of home-based nursing on morbidity in people infected with HIV/AIDS. Methods The trials studied are in HIV positive adults and children, regardless of sex or setting and all randomised controlled. Home-based care provided by qualified nurses was compared with hospital or health-facility based treatment. The following electronic databases were searched from January 1980 to March 2015: AIDSearch, CINAHL, Cochrane Register of Controlled Trials, EMBASE, MEDLINE and PsycINFO/LIT, with an updated search in November 2016. Two authors independently screened titles and abstracts from the electronic search based on the study design, interventions and types of participant. For all selected abstracts, full text articles were obtained. The final study selection was determined with use of an eligibility form. Data extraction was performed independently from assessment of risk of bias. The results were analysed by narrative synthesis, in order to be able to obtain relevant effect measures plus 95% confidence intervals. Results Seven studies met the inclusion criteria. The trial size varied from 37 to 238 participants. Only one trial was conducted in children. Five studies were conducted in the USA and two in China. Four studies looked at home-based adherence support and the rest at providing home-based psychosocial support. Reported adherence to antiretroviral drugs improved with nurse-led home-based care but did not affect viral load. Psychiatric nurse support in those with existing mental health conditions improved mental health and depressive symptoms. Home-based psychological support impacted on HIV stigma, worry and physical functioning and in certain cases depressive symptoms. Conclusions Nurse-led home-based interventions could help adherence to antiretroviral therapy and improve mental health. Further larger scale studies are needed, looking in more detail at improving medical care for HIV, especially related to screening and management of opportunistic infections and co-morbidities.